A cost analysis of road traffic injuries in a tertiary hospital in south-west Nigeria. Issue 4 (2nd October 2017) - Urua, Uduak; Osungbade, Kayode; Obembe, Taiwo; Adeniji, Folashayo
Abstract : This study examines the burden of road traffic injuries (RTIs) among road crash victims in a tertiary hospital in Ibadan, Nigeria. The study adopted a purposive sampling method to obtain primary data. Interview was done with 266 RTI victims who were admitted to the University College Hospital, Ibadan and discharged between March and May, 2015, using a structured questionnaire. From the data obtained, the study carried out descriptive statistical analyses. The results showed that the average cost per patient for RTI treatment was ₦ 42, 946 ($215.9); on average, the amount expended on surgery was the highest followed by wound dressing and drugs; and the prevalence of catastrophic out-of-pocket (OOP) expenditure was over 86%. It is recommended that given the high burden of OOP hospital expenditure associated with RTI, there is need to implement more effective financial protection mechanisms against the high OOP expenditure faced by crash victims.